Health & Safety Practices in the Western Australian mining Industry - Jansz, Janis (Technical University of Ostrava, 2012)
This article traces the history of health and safety practices in the Western Australian mining industry from the mining performed by the Aboriginal people to the mining industry work in 2012. It identifies the success strategies that have made the Western Australian mining industry a world leader in having a high standard of workplace health and safety practices.